Christian expatriates in Muslim lands: the many roles of Aragonese mercenaries in Medieval Northern Africa - Jaspert, Nikolas (Military diasporas, 2023)
In a comprehensive survey spanning the period between the eleventh and fifteenth centuries, this chapter attempts to uncover the multiple and variable modes of identity that marked the activities of Iberian Christian mercenaries under Muslim rule. Focusing on notions of belonging across the religious divide, it shows the extent to which Christian expatriates remained loyal to their former feudal overlords and how different forms of alterity affected their “embeddedness” and thus their status in the Muslim host society. The unusually detailed explicit sources still extant in Iberian archives reveal insights into the social life and mindsets of displaced soldiers in the Middle Ages. Precisely due to their religious affiliation, Christian mercenaries in Northern African polities fulfilled functions that by far transcended the military field. Some of these militiamen could serve as go-betweens or even cultural brokers, developing considerable agency in the arena of diplomacy; some converted to Islam, while others created kinship groups and even founded dynasties of Christian mercenaries in foreign lands